(untitled) (Czech Journal of International Relations, 2025)
Existing studies of radical right-wing populism have primarily analysed populist leaders like Milei and Bolsonaro through their retrotopian appeals to past authoritarianism, often overlooking their forward-looking utopian projections. This gap in the literature obscures how their rejection of the status quo frames the climate crisis as a manufactured dystopia — one they counter by dismissing its very existence. Drawing on insights from utopian studies, this research seeks to fill this gap by providing tools for deconstructing the covert utopias envisioned by these leaders. Specifically, it examines how Jair Bolsonaro (2019-2022) and Javier Milei (2024-present) craft their utopian imaginaries and the role that environmental denial plays within them.